Modelling the Energy Demand of Households in a Combined Top Down/Bottom Up Approach - Kurt Kratena; Ina Meyer; Michael Wüger (Austrian Institute of Economic Research (WIFO), 2008)
This paper deals with integrating elements of a bottom-up model of energy demand into a top-down model of total private consumption. The bottom-up elements are represented by the energy efficiency embodied in household appliances. The top-down model describes demand for energy and non-energy commodities in an AIDS demand system. In this model households do not directly demand energy, but energy services (hours of washing, miles of driving). These services are measured via the service price defined as the relationship between the energy price and energy efficiency. Therefore an increase in energy efficiency leads to a decrease in the service price and, thereby, increases demand for services which compensates for parts of the energy savings due to efficiency improvements ("rebound effect"). The model presented can be used to derive different feedbacks (rebound effects) from efficiency changes on energy demand and to quantify the role of efficiency improvements in reducing energy demand and emissions from households.
Keywords: 330; household energy demand; rebound effects; efficiency of appliances; Energiekonsum; Privater Haushalt; Nachfragesystem; Energieeinsparung; Österreich